1986
DOI: 10.3171/jns.1986.64.2.0231
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics in patients with acute severe head trauma

Abstract: Mean hemispheric cerebral blood flow (CBF) was studied in 11 comatose brain-injured patients following intravenous administration of xenon-133. Repeated measurements were performed in order to evaluate cerebral vasoreactivity following a decrease in PaCO2. In addition, the effect of induced barbiturate coma was evaluated in patients with intracranial hypertension. The cerebral vasoreactivity and the CBF response following induction of barbiturate coma varied. In patients with normal CO2 reactivity, barbiturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 23 publications
4
34
0
2
Order By: Relevance
“…Current treatments are frequently aimed at reducing intracranial pressure and depend on cerebral vasoreactivity. 18,19 In severe bacterial meningitis, however, cerebral blood flow (CBF) autoregulation is often damaged. Furthermore, cerebral metabolic oxygen demand (CMRO 2 ) and CBF coupling is frequently disrupted and leads to multisegmental hypoperfusion or hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments are frequently aimed at reducing intracranial pressure and depend on cerebral vasoreactivity. 18,19 In severe bacterial meningitis, however, cerebral blood flow (CBF) autoregulation is often damaged. Furthermore, cerebral metabolic oxygen demand (CMRO 2 ) and CBF coupling is frequently disrupted and leads to multisegmental hypoperfusion or hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that it is not possible to distinguish these patients by clinical examination or with CT brain scan. The effects of conventional symptomatic treatment (osmotic diuresis, thiopental, hyperventilation) are greatly dependent (or associated with) on cerebral arterioles vasoreactivity [27]. Patients with impaired CO 2 R are candidates for therapeutic hypothermia (TH).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies with larger numbers of patients that are designed to evaluate the impact of MOI on CO 2 R and outcome are needed. Multiple studies involving adult patients have shown a link between poor neurological outcomes and impaired CO 2 R. 8,13,[19][20][21]28 One pediatric study found patients with higher mean CO 2 R trended toward a more favorable outcome, and CO 2 R < 2%/torr PaCO 2 in the first 48 hours after injury was correlated with poor neurological outcome at 6 months after injury.…”
Section: Outcome Correlationmentioning
confidence: 99%